Fat metaplasia and backfill are key intermediaries in the development of sacroiliac joint ankylosis in patients with ankylosing spondylitis - Walter P. Maksymowych (2018)
Copyright © 2014 by the American College of Rheumatology. Objective Fat metaplasia in bone marrow on T1-weighted magnetic resonance imaging (MRI) scans may develop after resolution of inflammation in patients with ankylosing spondylitis (AS) and may predict new bone formation in the spine. Similar tissue, termed backfill, may also fill areas of excavated bone in the sacroiliac (SI) joints and may reflect resolution of inflammation and tissue repair at sites of erosions. The purpose of this study was to test our hypothesis that SI joint ankylosis develops following repair of erosions and that tissue characterized by fat metaplasia is a key intermediary step in this pathway. Methods We used the Spondyloarthritis Research Consortium of Canada (SPARCC) SI structural lesion score (SSS) method to assess fat metaplasia, erosions, backfill, and ankylosis on MRIs of the SI joints in 147 patients with AS monitored for 2 years. Univariate and multivariate regression analyses focused first on identifying significant MRI predictors of new backfill and fat metaplasia. We then assessed the role of backfill and fat metaplasia in the development of new ankylosis. All analyses were adjusted for demographic features, treatment, and baseline and 2-year change in SSS values for parameters of inflammation and MRI structural lesions. Results Resolution of inflammation and reduction of erosions were each independently associated with the development of new backfill and fat metaplasia at 2 years on multivariate analyses. Multivariate regression analysis that included demographic features, baseline and 2-year change in parameters of inflammation and MRI structural lesion showed that reduction in erosions (P = 0.0005) and increase in fat metaplasia (P = 0.002) at 2 years was each independently associated with the development of new ankylosis. Conclusion Our data support a disease model whereby ankylosis develops following repair of erosions, and fat metaplasia and backfill are key intermediary steps in this pathway.